A study on Cr(VI) reduction from aqueous solutions by bauxite - Turan, M. D.; Altundogan, H. S. (Journal of Central South Univ Technology, 2014)
The reduction of Cr(VI) in aqueous solution by using bauxite ore was investigated. Experimental results for Cr(VI) reduction in aqueous solution depending on some factors such as time, sulfuric acid amount, bauxite dosage, initial Cr(VI) concentration, formic acid concentration, daylight and temperature were presented. The obtained results show that sulfuric acid amount, bauxite dosage and initial Cr(VI) concentration of solution are most effective parameters on the reduction process. Also, it has been found that the 60 g/L of bauxite dosage is sufficient to reduce up to 100% of Cr(VI) from acidic solution under the condition of low initial Cr(VI) mass concentrations such as 10 mg/L. The reduction reaction is completed within 30 min at 25 A degrees C under the experimental conditions: bauxite dosage of 60 g/L, amount of sulfuric acid 40-60 stoichiometric and initial mass concentration of Cr(VI), 10 mg/L. It was determined that reduction percentage is decreasing with increasing initial Cr(VI) concentration. The chemical oxygen demand of bauxite ore was found to be 26 mg COD/g.
Keywords: bauxite ore; chromium; reduction; sulfuric acid